Dietary supplementation with hydrolyzed yeast and its effect on the performance, intestinal microbiota, and immune response of weaned piglets - Berto, Patrícia N.; Tse, Marcos L. P. [UNESP]; Ramos, Dênis R. A. [UNESP]; Saleh, Mayra A. D.; Miassi, Gabriela M. [UNESP]; Yamatogi, Ricardo S.; Berto, Dirlei A. [UNESP]; Trindade Neto, Messias A. (FapUNIFESP (SciELO), 2020)
The objective of this study was to evaluate the effects of autolyzed yeast on performance, cecal microbiota, and leukogram of weaned piglets. A total of 96 piglets of commercial line weaned at 21-day-old were used. The experimental design was a randomized block design with four treatments (diets containing 0.0%, 0.3%, 0.6%, and 0.9% autolyzed yeast), eight replicates, and three animals per pen in order to evaluate daily weight gain, daily feed intake, and feed conversion in periods of 0 to 15, 0 to 26, and 0 to 36 days. Quadratic effects of autolyzed yeast inclusion were observed on the feed conversion from 0 to 15 days, on daily weight gain from 0 to 15 days, 0 to 26 days and, 0 to 36 days, indicating an autolyzed yeast optimal inclusion level between 0.4% and 0.5%. No effect from autolyzed yeast addition was observed on piglet daily feed intake, cecal microbiota, and leukogram; however, i.m. application of E. coli lipopolysaccharide reduced the values of total leukocytes and their fractions (neutrophils, eosinophils, lymphocytes, monocytes, and rods). Therefore, autolyzed yeast when provided at levels between 0.4% and 0.5% improved weaned piglets’ performance.
Keywords: Immune system; Leukogram; Nutrition; Swine; Weaning